2010
DOI: 10.1039/c0dt00399a
|View full text |Cite
|
Sign up to set email alerts
|

Chiral undecagold clusters: synthesis, characterization and investigation in catalysis

Abstract: Enantiopure undecagold clusters protected by chiral atropisomeric diphosphine ligands (P^P) have been synthesized by the stoichiometric reduction of the corresponding (P^P)(AuCl)(2) complexes with NaBH(4). The molecular mono-disperse [Au(11)(P^P)(4)Cl(2)]Cl species have been thoroughly characterized using an array of analytical techniques. (31)P NMR experiments suggested the presence of a slow intramolecular ligand exchange process. Circular dichroism measurements showed that enantiomeric clusters display mirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“…Interestingly, for both cases discussed above, the anisotropy factor was reported to be larger (by a factor of 3) for particles directly prepared with the respective thiols, than for those obtained via the ligand exchange method. Thus, apparently only a few chiral ligands are needed to induce significant optical activity in the metalbased electronic transitions [63,66]. All these observations are consistent with a chiral footprint model (mechanism (c)).…”
Section: Nanoparticles With Individual Dissymmetrysupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, for both cases discussed above, the anisotropy factor was reported to be larger (by a factor of 3) for particles directly prepared with the respective thiols, than for those obtained via the ligand exchange method. Thus, apparently only a few chiral ligands are needed to induce significant optical activity in the metalbased electronic transitions [63,66]. All these observations are consistent with a chiral footprint model (mechanism (c)).…”
Section: Nanoparticles With Individual Dissymmetrysupporting
confidence: 78%
“…The use of chiral ligands in the proximity of nanoclusters and nanoparticles has already led to the synthesis of important novel nanomaterials with individual dissymmetry, such as intrinsically chiral nanoparticles [54,55], capped nanocrystals with a chiral distribution of the electron density [61,75], and footprinted nanoparticles [64,65]. Although still in their infancy, these systems have shown very high catalytic activity and enantioselectivity toward several organic transformations [66,143], and can be considered potential electrochemical [144], VCD [57], and SEROA (surface enhanced Raman optical activity) [145] sensors. However, the potential uses of nanoparticles with individual chirality as a plasmonic material [52,76] is still hindered primarily due to limitations in colloidal synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…We have also found that the simple NaBH 4 reduction of Au 2 (dppp)Cl 2 in ethanol gives 30 as the main cluster product (f) [69]. On the other hand, the mass spectrometric analyses of the reduction system Au(PPh 3 [71] and MeO-BIPHEP [72] in ethanol (h), which are identified by mass and absorption spectra but their single-crystal X-ray structures are not available.…”
Section: Scheme 5 Examples Of Simple Ligand-exchange Reactionmentioning
confidence: 99%
“…12,13 Despite the ever burgeoning literature concerning gold-catalysed reactions, the majority of structurally defined chiral gold complexes are restricted to those bearing chiral phosphane ligands. [14][15][16][17][18][19] Given the fact the use of gold-NHC complexes [20][21][22][23][24][25][26] is now de rigour in synthesis, it is somewhat surprising that reports of structurally characterised, chiral, Au(I)-NHC [27][28][29][30][31][32][33][34][35][36] and Au(I)-ADC/NAC 37 complexes are still comparatively scarce. Likewise, the synthesis and characterisation and catalytic activity of cyclometallated gold(III) complexes is relatively unexplored, with only a handful of examples being cited in the literature.…”
Section: Introductionmentioning
confidence: 99%